Development of a Wine Yeast Strain Capable of Malolactic Fermentation and Reducing the Ethyl Carbamate Content in Wine - Egor A. Vasyagin; Valery N. Urakov; Maksim Yu. Shalamitskiy; Sofia N. Cherviak; Elena V. Ivanova; Valentina I. Zagoruyko; Alexey V. Beletsky; Andrey L. Rakitin; Eugenia S. Mardanova; Vitaly V. Kushnirov; Nikolai V. Ravin; Andrey V. Mardanov (Foods)
In winemaking, malolactic fermentation (MLF), which converts L-malic acid to L-lactic acid, is often applied after the alcoholic fermentation stage to improve the sensory properties of the wine and its microbiological stability. MLF is usually performed by lactic acid bacteria, which, however, are sensitive to the conditions of alcoholic fermentation. Therefore, the development of wine yeast strains capable of both alcoholic fermentation and MLF is an important task. Using genome editing, we engineered a modified variant of the triploid wine yeast strain Saccharomyces cerevisiae I-328, in which the CAR1 arginase gene was replaced by the malate permease gene from Schizosaccharomyces pombe and the malolactic enzyme gene from Oenococcus oeni. Genome-wide transcriptional profiling confirmed the expression of the introduced genes and revealed a limited effect of the modification on global gene expression. Winemaking experiments show that genome editing did not affect fermentation activity and ethanol production, while use of the modified strain resulted in a tenfold reduction in malate content with simultaneous formation of lactate. The resulting wines had a softer and more harmonious taste compared to wine obtained using the parental strain. Inactivation of arginase, which forms urea and L-ornithine through the breakdown of arginine, also resulted in a twofold decrease in the content of urea and the carcinogenic ethyl carbamate in wine. Thus, the new strain with the replacement of the arginase gene with the MLF gene cassette is promising for use in winemaking.